2013
DOI: 10.1039/c2cc37360b
|View full text |Cite
|
Sign up to set email alerts
|

Great improvement of catalytic activity of oxide counter electrodes fabricated in N2 atmosphere for dye-sensitized solar cells

Abstract: The dye-sensitized solar cells (DSCs) using SnO(2) and Nb(2)O(5) counter electrodes (CEs) prepared in N(2) atmosphere yielded power conversion efficiencies (PCE) of 6.09% and 4.65%, much higher than the PCE values (1.84%, 0.97%) of the DSCs using the same SnO(2) and Nb(2)O(5) CEs prepared in air.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 21 publications
(19 reference statements)
0
25
0
Order By: Relevance
“…Unlike the semiconductor, dye, and redox shuttle components, counter electrode (CE) catalysts are often overlooked. Fortunately, CE catalysts begun to attract increasing attention, as a class of new CE catalysts, such as carbon materials, [9][10][11][12] organic polymers, [13][14][15][16] and metal compounds [17][18][19][20][21][22][23][24][25][26][27][28][29][30] have been applied to replace conventional noble Pt CE. Among these Pt-free materials, carbon is a promising CE catalyst for use in DSCs because of its low cost, high conductivity, high catalytic activity, ready availability, high thermal stability, and corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the semiconductor, dye, and redox shuttle components, counter electrode (CE) catalysts are often overlooked. Fortunately, CE catalysts begun to attract increasing attention, as a class of new CE catalysts, such as carbon materials, [9][10][11][12] organic polymers, [13][14][15][16] and metal compounds [17][18][19][20][21][22][23][24][25][26][27][28][29][30] have been applied to replace conventional noble Pt CE. Among these Pt-free materials, carbon is a promising CE catalyst for use in DSCs because of its low cost, high conductivity, high catalytic activity, ready availability, high thermal stability, and corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, inorganic metal compounds based Pt-free catalysts for use in DSSCs developed rapidly, such as carbides [17][18][19][20][21][22][23], nitrides [24][25][26], oxides [27][28][29], sulfides [30][31][32][33][34][35][36][37] as well as selenides [38][39]. For example, Yang et al reported low cost Sn x S CE for DSSCs and demonstrated comparable power conversion efficiency to Pt [40].…”
Section: Introductionmentioning
confidence: 99%
“…However, the low abundance and high cost of Pt noble metal has restricted the large-scale commercialization of DSSCs. Therefore, considerable efforts have been made on developing low cost Pt-free catalytic materials on the purpose of making DSSCs more competitive for future commercialization and simultaneously maintaining the good performance [17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…These oxides may be further improved by changing their electronic structure. Hydrogen (H 2 ) or nitrogen (N 2 ) treatments have been proved to be a facile and efficient method to change the electronic structure of oxides, with which the efficiencies were improved from 0.63% to 5.43% for WO 3 by H 2 treatment and from 1.84% to 6.09% for SnO 2 by N 2 treatment [14,15]. However, the DSCs using these CEs still yield low fill factors (FF) and low efficiencies as compared to conventional Pt CEs; further improvements need to be carried out.…”
Section: Introductionmentioning
confidence: 99%